Kajian Kelayakan Penambahan Fuel Gas Heatergas Turbin Tipe M701D Untuk Meningkatkan Effisiensi PLTGU Grati - Vendy Antono; Retno Aita Diantari; Yudi Kriswanto (JURNAL POWERPLANT, 2015)
PT Indonesia Power UBP Perak RoW have six gas turbines with a capacity of 100 MW each in which the fuel used is natural gas. One of the things that is very considered in the generation of electricity is the efficiency of an equipment, the observation that we encounter in the gas turbine efficiency is still relatively low, wasting fuel and have high production costs. To overcome this, the existing power plant should need to improve the efficiency of the total system that will reduce fuel consumption and production costs. In this case, one way to improve the efficiency of gas turbine type M701 D by adding a fuel gas heater (FGH) to absorb most of the heat in the exhaust (waste heat) through the Rotor Cooling Water (RCA) utilized to heat the fuel before entering into the gas turbine, without reducing the functionality of the cooling system of the gas turbine is even improve the functioning of the RCA itself, it aims to minimize waste heat are dumped into the atmosphere is not too large so that the efficiency of the system at the Gas Turbine increased overall, lower fuel consumption so that the production cost becomes less. Having done a comparison of calculation before and after FGH fitted with a variety of load Gas Turbine in getting power output increase by 1.11% - 1.37% and the efficiency of gas turbines rose by 0.25% - 0.39% and a decrease in heat rate ranging between 0.8% - 1.47%.